Several Factors Associated With Nitrogen Balance In Elderly Patients - Zurriyani Zurriyani; Jusri Ichwani; Novira Widajanti (Universitas Airlangga, 2020)
BackgroundNitrogen balance is the method used to assess the protein adequacy. A negative nitrogen balance means that the body suffers from protein energy malnutrition.ObjectiveTo determine the risk factors that associated with nitrogen balance in the elderly patients who were inpatient in IRNA Internal Medicine Dr.Soetomo Hospital.MethodsThe experimental design of the research used was analytic observational with the cross-sectional design. The study was conducted of 50 elderly patients. Risk factors measured were protein intake using food recall and nitrogen excretion that expressed in Urea Nitrogen Urine (gr / 24 h). The nitrogen balance was derived from the difference between nitrogen intake and nitrogen excretion in 24 hours. Bivariate data analysis using Chi square or exact fisher test, while multivariate data analysis using logistic regression test.ResultsIn bivariate analysis, risk factors significantly associated with negative nitrogen balance were decreased renal function (LFG <90 ml / min / 1.73 m2), prolonged bed rest> 7 days and malnutrition. Other risk factors not significantly associated with negative nitrogen balance were diabetes mellitus, random blood sugar> 180 mg / dl, hypoalbumin and CRP> 6 mg / dl. In multivariate analysis showed the decrease of renal function and duration of bed rest > 7 days was significant.ConclusionThe decreased renal function and bed rest for more than 7 days was a risk factor for protein malnutrition in elderly patients.